HUBUNGAN PRAKTIK PENGASUHAN TERKAIT HIGIENE SANITASI DENGAN STATUS GIZI BALITA - Andigna Puspita Purnama; Dini Ririn Andrias (JURNAL PENELITIAN KESEHATAN, 2016)
Nutritional status of children underfive is one of the achievment indicators of health sector development. Suboptimalnutritionalstatusofchildrenunderfiveblocks the cognitive development and influences health status onadult age. In relation to child care, parents are the closest environment for children. Thus, care practice is thebasis of the development of an individual carried out by parents. The purpose of this research is to analyze theassociation of child care practices related to hygiene and sanitation and nutritional status of children underfive.The research was an analytical observation with cross sectional design. The sample size was 52 childrenunderfive age 24-60 months, which were taken from the three villages in Prambon public helath center areaKabupaten Nganjuk, proportionally based on the highest number of children underfive in the villages, usingproportional random sampling method. Primary data were collected through interview by using questionnairesand through observation. Chi-square test was used in the statistical analysis. The result of the research showedthat there was a relation of child care practices related to hygiene and sanitation Keywords: care, hygiene and sanitation, nutritional status